2017
DOI: 10.1038/srep42881
|View full text |Cite
|
Sign up to set email alerts
|

Successive extraction of As(V), Cu(II) and P(V) ions from water using spent coffee powder as renewable bioadsorbents

Abstract: For the first time, renewable and easy accessible pre-bleached spent coffee powder coated with polyethylenimine (PEI) and ferric ions (Coffee-PEI-Fe) was used for the successive adsorption of As(V), Cu(II) and P(V) ions from spiked water samples. Fully characterized coffee-PEI-Fe was employed for batch mode experiments. Kinetic regression analysis showed that the adsorption processes of As(V) and P(V) anions follows a pseudo-second-order model, while the adsorption of Cu(II) ions fit with a pseudo-first-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Diverse methods are being developed for water remediation, including use of plant biomass 18 20 . Work by Rezania (2015) and others have reported the potential of water hyacinth in the removal of pollutants from an aqueous solution 21 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Diverse methods are being developed for water remediation, including use of plant biomass 18 20 . Work by Rezania (2015) and others have reported the potential of water hyacinth in the removal of pollutants from an aqueous solution 21 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Some research showed that coffee grounds effective binding Pb (II) ions in the water [21]. The coffee grounds can adsorb the Cu (II) dan Cr (VI) [22] and adsorb As (v), Cu (II) dan P (v) [23] in the aqueous. The dried coffee grounds also can adsorb Pb, Cr and Cd [24] The adsorbsi-desorbsi occures caused by the mechanism of ion exchange of the heavy metals [25].…”
Section: Results and Disscusionmentioning
confidence: 99%
“…where K 2 (g/mg min) is the equilibrium rate constant for the pseudo second-order adsorption, whereas q e can be calculated from the plot of t/q t against t (Figure 8b) [42]. A comparison of the results with the correlation coefficients for the first and second order models is listed in Table 3.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…The third portion is the final equilibrium stage, where the adsorbate has extremely low concentrations in the solution due to the slowing down of intraparticle diffusion.   (5) where K2 (g/mg min) is the equilibrium rate constant for the pseudo second-order adsorption, whereas qe can be calculated from the plot of t/qt against t (Figure 8b) [42]. A comparison of the results with the correlation coefficients for the first and second order models is listed in Table 3.…”
Section: Adsorption Kineticsmentioning
confidence: 99%